(untitled) (Research, Society and Development, 2023)
Objective: To analyze the importance of professional responsibility and patient safety during dental procedures performed at the dental school of the University of Cuenca. Methodology: A cross-sectional descriptive observational study was carried out using a validated questionnaire based on the key dimensions of the SERVQUAL model to 50 patients between 18 and 65 years of age, who attend the undergraduate clinic of the Faculty of Dentistry of the University of Cuenca during the period March 2023-August 2023, where questions aimed at finding out the management of professional responsibility and patient safety during dental care were addressed. Results: Results were obtained from 50 surveys; in which it was determined that patients are satisfied with the biosafety management offered by students during dental procedures. On the other hand, the patients expressed dissatisfaction with the technological advances used by the students in the different areas during dental care. Conclusion: It is recommended to improve the technological advances during dental procedures, since the patients were able to indicate that there is a deficiency in this area.